Iron deficiency anaemia in sub-Saharan Africa: a review of current evidence and primary care recommendations for high-risk groups. Issue 10 (October 2021) - Mwangi, Martin N; Mzembe, Glory; Moya, Ernest; Verhoef, Hans
Summary: The epidemiology of iron deficiency anaemia in sub-Saharan Africa differs from that in other parts of the world. The low-quality diets prevalent in this region are a poor source of iron, the population is frequently exposed to infection, and demographic characteristics result in a greater prevalence of people at high risk of iron deficiency anaemia than in other parts of the world. We herein review the causes, disease burden, and consequences of iron deficiency anaemia in the general population in this region, and current policies and interventions for its control. The current debate is dominated by concerns about the safety of iron interventions, namely regarding its effects on malaria and other infectious diseases. However, universal antenatal iron supplementation and delayed cord clamping are safe interventions and stand out for their potential to improve maternal and infant health. Effective infection control is a precondition to safe and efficacious iron interventions in children. Greater emphasis should be given to approaches aiming to reduce iron loss due to helminth infections and menstruation, alongside interventions to increase iron intake. Translation: For the French translation of the abstract see Supplementary Materials section.